Epileptiform abnormalities in non-epileptic children with ADHD: Correlation with clinical subtypes - Elsayed, Riad M.; Sayyah, Hala E.; Zakarya, Sheeren (Journal of Pediatric Neurology, 2012)
There is high prevalence rate of attention deficit/hyperactive disorders (ADHD), and there is vague relation between it and epileptiform abnormalities. The objective of this study is to assess the relation between epileptiform abnormalities and ADHD. We studied 50 ADHD children and 25 sex and age matched controls. We used 20 channels electroencephalography under standard condition for assessing patients and control. ADHD rating scale was used for assessing patients. Epileptiform abnormalities were detected in 15 (30%) of ADHD children, in comparison with two (8%) of control group (P < 0.005). While, we did not find any correlation between ADHD subtypes and pattern of epileptiform discharge.
Keywords: Epileptiform abnormalities; non-epileptic; children; ADHD